Drilling and Producing – Equipment, Methods, and Materials - Corrosion of Oil Well Casing by Earth Currents - Leendert de Witte; Fred J. Radd (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1956)
In many areas caring failures can be directly related to electrical currents observed in the casings. It is the thesis of this paper that the observed casing currents are mainly due to electrochemical potentials of the type in evidence on spontaneous potential curves of electrical logs. The general nature of these potentials are discussed and an equivalent circuit is given for current and potential distributions around open holes. The casing forms a short circuit to these potentials and tends to average the effects of local cells. The case of casing corrosion opposite the Dakota water sands in the salt-mud area of Kansas is discussed anil used us a qualitative, illustration of the relation between SP's and casing currents. A method of quantitative derivation of casing current distribution frorn electric log SP curves, using linear transform theory, is described and results are compared with a measured current profile. The effects of hydrogen over-potentials at the cathodic portions of the pipe are considered and some laboratory data are given in support of conclusions regarding the over-1.01tuge.s. INTRODUCTION To date an appreciable amount of work has been done on the measurement of oil well casing currents and on the correlation of the anodic portions of the current profiles with corrosive casing failures. Speculations on the origin of the casing currents have, however, remained rather vague; and although almost every plausible cause has been mentioned, there is to the writers' knowledge no clear-cut expose' on the details of the causes of the corrosive currents in the literature. A study of current surveys and casing failures in the N.W. Burnett field, Ellis County. Kan.. indicated the probability that concentration cell emf's between the Wellington salt section and the relatively fresh waters in the Dakota sands were a major cause of the corrosion currents. A more general concept evolved upon analysis of the severe corrosive conditions in the Pleistocene sands in the Ventura Avenue and San Miguelito fields in California. In this area no major variations in the salt content of the formation waters occur and yet large casing currents are observed. An explanation is found in the fact that the local spontaneous potentials which are set up due to concentration contrast between the drilling fluid and the connate water are short circuited when casing is set. The very conductive path through the casing increases the magnitude of the currents and has the tendency to average local sources over fairly large intervals. Current will flow between the sections that are predominently shaly and the sections that are mostly sandy. At the places where the current leaves the pipe, corrosive attack will occur. This same phenomenon will be present wherever unprotected pipe is set through sections that show large SP kicks on the electric logs over reasonably thick interval~. GENERAL- NATURE OF THE SPONTANEOUS POTENTIALS When a sequence of sedimentary rocks is penetrated by a drill hole filled with a mud which has a different salt concentration from that in the formation waters, various types of electrochemical potentials are established between the formations and different parts of the mud column. Opposite clean sand sections. a simple liquid-liquid junction potential will be observed; while opposite argillaccous formations, a membrane potential, often referred to as shale potential, will be established. The first quantitative analysis of these emf's in terms of liquid junction and membrane potentials is due to Wyllie.1